1997
DOI: 10.1038/sj.ijo.0800446
|View full text |Cite
|
Sign up to set email alerts
|

Predicting intra-abdominal fatness from anthropometric measures: the influence of stature

Abstract: OBJECTIVE: To investigate the in¯uence of height on the relationships between the intra-abdominal fat and anthropometric measures. SUBJECTS: Twenty healthy female volunteers aged 20±51 y from Aberdeen, and 71 men and 34 women aged 19±85 y from Nijmegen, The Netherlands. OUTCOME MEASURES: Intra-abdominal fat volumes by magnetic resonance imaging (MRI) in Aberdeen and crosssectional areas at L4-L5 level by computerised tomography (CT) in Nijmegen, height, body mass index (BMI), waist circumference, waist sagitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
1
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(120 citation statements)
references
References 17 publications
6
108
1
5
Order By: Relevance
“…Abdominal obesity, assessed by waist-to-hip ratio or waist circumference for given BMI, has been found to be a better predictor of death than BMI alone, as it captures the harmful abdominal fat. 54,57,58 However, our data from 1976-1978 and 1981-1983 did not include measures of waist and hip circumferences. In addition, we did not have information on either age of obesity onset, duration of obesity, type of lost tissue, whether the weight loss was intended or not and whether it was maintained or not.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…Abdominal obesity, assessed by waist-to-hip ratio or waist circumference for given BMI, has been found to be a better predictor of death than BMI alone, as it captures the harmful abdominal fat. 54,57,58 However, our data from 1976-1978 and 1981-1983 did not include measures of waist and hip circumferences. In addition, we did not have information on either age of obesity onset, duration of obesity, type of lost tissue, whether the weight loss was intended or not and whether it was maintained or not.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…13 Waist circumference, on the other hand, is highly correlated with intra-abdominal fat volumes determined by magnetic resonance imaging, 14 and predicts increased mortality beyond that accounted for by BMI. 15 BMI was calculated by dividing weight in kilograms by the square of height in metres.…”
Section: Anthropometrymentioning
confidence: 99%
“…Our previous MRI study of twenty women, has shown that a single cut at two thirds the distance between xiphisternum and the anterior iliac crest, at approximately the L2±L3 level in most subjects, gave the highest correlation with intra-abdominal fat volume. 3 The present paper described a novel method for calculating extra-abdominal and intra-abdominal fat volumes from multiple MRI scans, and determined the level of a single transverse scan of intra-abdominal fat between L1 and L5 vertebrae, that best predicts intraabdominal fat volumes. Subjects with non-insulin dependent diabetes mellitus (NIDDM) were studied to extend the scope of intra-abdominal fat accumulation.…”
Section: Introductionmentioning
confidence: 99%